HIV/AIDS stigma among a sample of primarily African-American and Latino men who have sex with men social media users. Issue 6 (2nd June 2016) - Garett, Renee; Smith, Justin; Chiu, Jason; Young, Sean D.
ABSTRACT: The recent increase in social media use allows these technologies to rapidly reach communities with higher HIV prevalence, such as African-American and Latino men who have sex with men (MSM). However, no studies have looked at HIV/AIDS stigma among social media users from African-American and Latino MSM communities, or the association between stigma and social media use among these groups. This study sought to assess the level of HIV/AIDS stigma among a sample of social media-using African-American and Latino MSM from Los Angeles. A total of 112 (primarily African-American and Latino, n = 98, 88%) MSM Facebook users completed a survey on demographics, online social network use, and HIV/AIDS stigma. A composite stigma score was created by taking the cumulative score from a 15-item stigma questionnaire. Cumulative logistic models were used to assess the association between HIV/AIDS stigma and online social network use. In general, participants reported a low level of HIV/AIDS stigma (mean = 22.2/75, SD = 5.74). HIV/AIDS stigma composite score was significantly associated with increased time spent on online social networks each day (Adjusted odds ratios (AOR): 1.07, 95% CI: 1.00, 1.15). Among this diverse sample of MSM online social network users, findings suggest that HIV/AIDS stigma is associated with usage of social media. We discuss the implications of this work for future HIV prevention.